Slowed Temporal and Parietal Cerebrovascular Response in Patients with Alzheimer's Disease. (May 2020) - Holmes, Kenneth R.; Tang-Wai, David; Sam, Kevin; McKetton, Larissa; Poublanc, Julien; Crawley, Adrian P.; Sobczyk, Olivia; Cohn, Melanie; Duffin, James; Tartaglia, Maria Carmela; Black, Sandra E.; Fisher, Joseph A.; et al.
ABSTRACT: Background: Recent investigations now suggest that cerebrovascular reactivity (CVR) is impaired in Alzheimer's disease (AD) and may underpin part of the disease's neurovascular component. However, our understanding of the relationship between the magnitude of CVR, the speed of cerebrovascular response, and the progression of AD is still limited. This is especially true in patients with mild cognitive impairment (MCI), which is recognized as an intermediate stage between normal aging and dementia. The purpose of this study was to investigate AD and MCI patients by mapping repeatable and accurate measures of cerebrovascular function, namely the magnitude and speed of cerebrovascular response (τ) to a vasoactive stimulus in key predilection sites for vascular dysfunction in AD. Methods: Thirty-three subjects (age range: 52–83 years, 20 males) were prospectively recruited. CVR and τ were assessed using blood oxygen level-dependent MRI during a standardized carbon dioxide stimulus. Temporal and parietal cortical regions of interest (ROIs) were generated from anatomical images using the FreeSurfer image analysis suite. Results: Of 33 subjects recruited, 3 individuals were excluded, leaving 30 subjects for analysis, consisting of 6 individuals with early AD, 11 individuals with MCI, and 13 older healthy controls (HCs). τ was found to be significantly higher in the AD group compared to the HC group in both the temporal ( p = 0.03) and parietal cortex ( p = 0.01) following a one-way ANCOVA correcting for age and microangiopathy scoring and a Bonferroni post-hoc correction. Conclusion: The study findings suggest that AD is associated with a slowing of the cerebrovascular response in the temporal and parietal cortices.